ChemInform Abstract: Selenium‐Catalyzed Oxidative C(sp2)—H Amination of Alkenes Exemplified in the Expedient Synthesis of (Aza‐)Indoles. Issue 42 (October 2015) - Ortgies, Stefan; Breder, Alexander
Abstract Both ortho‐amino styrenes and vinylated aminopyridines are successfully used as substrates for the synthesis of a wide range of indoles and aza‐indoles, respectively.